Use of co-verbal gestures during word-finding difficulty among Cantonese speakers with fluent aphasia and unimpaired controls. Issue 2 (1st February 2019) - Kong, Anthony Pak-Hin; Law, Sam-Po; Cheung, Charis Ka-Yan
ABSTRACT: Background : Co-verbal gestures refer to hand or arm movements made during speaking. Spoken language and gestures have been shown to be tightly integrated in human communication. Aims : The present study investigated whether co-verbal gesture use was associated with lexical retrieval in connected speech in unimpaired speakers and persons with aphasia (PWA). Methods & Procedures : Narrative samples of 58 fluent PWA and 58 control speakers were extracted from Cantonese AphasiaBank. Based on the indicators of word-finding difficulty (WFD) in connected speech adapted from previous research and a gesture annotation system with independent coding of gesture forms and functions, all WFD instances were identified. The presence and type of gestures accompanying each incident of WFD were then annotated. Finally, whether the use of gesture was accompanied by resolution of WFD (i.e., the corresponding target word could be retrieved) was examined. Outcomes & Results : Employment of co-verbal gesture did not seem to be related to the success of word retrieval. PWA's naming ability at single-word level and their overall language ability (as reflected by the aphasia quotient of the Cantonese version of the Western Aphasia Battery) were found to be the two strongest predictors of success rate of resolving WFD. Conclusions : The Lexical Retrieval Hypothesis highlighting the facilitative functions of iconic and metaphoric gestures in lexical retrieval was not supported. Challenges in conducting research related to WFD, and the clinical implications in gesture-based language intervention for PWA were discussed.